Municipal Asset Management in China's Small Cities and Towns : Findings and Strategies Ahead - Campanaro, Alessandra; Masic, Joanna; Kaganova, Olga; Fan, Hongye; Abdelfattah, Hazem (World Bank, Washington, DC, 2017)
Chinese municipalities have developed a large stock of capital assets during a period of rapid growth and urbanization, but have yet to modernize asset management practices. Cities face challenges such as premature decline of fixed assets and spiking liabilities related to operating and maintaining assets. This paper evaluates the asset management practices in three selected small cities and towns in China, using a benchmarking assessment tool followed by an in-depth field assessment. The paper finds that overall performance is below half the international benchmark for good practice in all three cities. Management practices are considerably more advanced for land than for buildings and infrastructure. Key deficiencies in data availability and reporting, governance, capacity, and financial management indicate increased risks for local government finance and the delivery of public services. For small cities and towns where public revenues are often uncertain and limited, urban public services will be at risk of deterioration unless good asset management practices are put in place. The paper recommends strategic actions for upper and lower levels of government, to advance local asset management practices and facilitate the reform agenda.